Sport und Recht in der Antike - Harter-Uibopuu, Kaja (2014)
The volume deals with the juridical and institutional framework of athletic and artistic games from archaic Greece to late antique Rome. The agones’ rules and regulations, the funding by public contributions and wealthy private sponsors were approached as well as the athletes’ training and prizes and privileges, which determined the athletes’—and especially the winner’s— social status. Moreover attention was drawn onto the end of the classical Greek agones from a Roman perspective.The Second Vienna Colloquium on Ancient Legal History addressed the juridical and institutional framework of athletic and artistic games in classical antiquity. The chronological frame ranged from Archaic times to Late Antiquity (8th cent. BCE – 6th cent. CE). The symposium covered three main areas of interest. Firstly, the agones’ rules and regulations, the funding by public contributions and wealthy private sponsors as well as the athletes’ training were approached. Prizes and privileges, which determined the athletes’—and especially the winner’s— social status and were thus crucial to the agones’ appeal, were then attended to by several papers. In contrast to the conditions under the Imperium Romanum, where the emperor enforced nation-wide regulations, the „politics of sports“ followed different rules in the small-scaled world of the classical Greek poleis. Thus, differences in the conception of sports between Greeks and Romans were traced and exemplarily demonstrated on the basis of the gladiatorial games. Lastly, attention was drawn onto the end of the classical Greek agones from a Roman perspective. The now Christian empire couldn’t tolerate the pagan agones anymore and instead developed new forms of athletic competitions and public entertainment: late antique circus games and chariot ra ...